Decision-Making on Deferred Statistical Convergence of Measurable Functions of Two Variables (Contemporary Mathematics, 2024)
In this paper, we define and study strongly deferred Cesàro summable, strongly Cesàro summable, m-statistical convergence and m-deferred statistical convergence of real-valued Lebesgue measurable functions of two variables. Further, we present illustrative examples in support of our definitions. Also, we examine some properties and relations among these concepts under some restrictions. In addition, we present illustrative examples to show the essentiality of these restrictions.
Keywords: lebesgue measure; statistical convergence; deferred statistical convergence; strongly deferred cesàro mean